MEMPROGRAMKAN PENGENALAN BANK SYARIAH DAN LEMBAGA KEUANGAN MIKRO SYARIAH DI DESA SUKAJADI, KECAMATAN TAMANSARI, KABUPATEN BOGOR - Ria Kusumaningrum; Muhamad Rizal; Afina Putri Nabilla (SAHID DEVELOPMENT JOURNAL, 2022)
The characteristics of Islamic banking are different from banking which is based on an interest system, Islamic banking is actually based on the core product of profit-sharing financing developed in musyārakah and muḍārabah financing products. The presence of Islamic banking should have a big impact on the growth of the real sector. One of the business units that needs to be developed to encourage growth in the real sector is Micro, Small and Medium Enterprises (MSMEs), which in the current national economy have a very important position, because of their contribution to employment and Gross Domestic Product (GDP), as well as flexibility and resilience in the face of economic crises. Islamic banking financing allocated to MSMEs in Bogor has experienced a fluctuating increase, but its contribution to increasing Micro, Small and Medium Enterprises has not been optimal. Islamic banking financing in Bogor has quite encouraging prospects in view of the quantity of MSMEs that have not yet obtained financing facilities. It is within this framework that community service is carried out by programming the introduction of Islamic banks and Islamic microfinance institutions in Sukajadi Village, Tamansari District, Bogor Regency from July to August 2020.